Imaginário do amor e da natureza: mitocrítica das criações de estudantes de Artes Visuais/IFPE - Santos, Analine Inês de Carvalho (2023)
This research aims to identify symbols, mythemes and myths in the visual creations of eight students enrolled between 2020 and 2021 in the Technical Course in Visual Arts (CTAV) at the Federal Institute of Education, Sciences and Technology of PE/Campus Olinda, in the subsequent modality. IFPE/Campus Olinda welcomes students from different social classes, ethnicities and gender, making it an eclectic, welcoming and multicultural space. To study the images in the visual creations of the interlocutors, I was based on the Imaginary Theory, in order to identify symbols, mythemes and myths. Critical knowledge, artistic practice and contextualization of images were actions that led to the germination of possibilities for understanding the path of creation. The research began with students enrolled in 2022 and they sent me 124 images, including paintings, drawings, sculptures and digital photomontages, as data for the investigation, in addition to the contribution of semi-structured interviews and intervention through online communication networks (WhatsApp and email). Gilbert Durand, Bachelard, Barbosa, Ostrower, bell hooks, Cirlot, Chevalier, Gheerbrant, Bachelard, Barcellos and other authors in the fields of art/education, creativity and imagination served as enriching sources for this research. Mitocriticism was used as a methodological path. A more sensitive look was used as a founding element to identify the imaginary in the art/education space at Campus Olinda. The discovery of the tree archetype is also present throughout the text, as well as in the imagery present in the environment of artistic creation.